Evaluation of ventilation performance and energy efficiency of greenhouse fans - Zhi, Zhang; Gates, Richard S; Zhirong, Zou; Xiaohui, Hu (International Journal of Agricultural and Biological Engineering, 2015)
In order to investigate fan performance in fan-ventilated greenhouses (Urbana, USA), the effects of guard screen and loose belts on fan ventilation airflow and power consumption in greenhouse operations were examined with four belt-driven fans as trial subjects. The Fans Assessment Numeration System was used to measure the airflow rate. Temperature, relative humidity and power consumption were also monitored. Results show there were significant differences in the airflow rate between the fans with a cleaned and uncleaned guard screen [P is less than 0.05]. Power consumption also differed significantly even with the same cooling effect in greenhouse. When fan belts were adjusted to the proper tension, the fan speed and airflow rate were 13.1% and 30.1% higher than those of original belts, respectively. The daily average power consumption for the fan with the original loose belts was 20.4% higher than that with the adjusted belts when the pad was not working and 24.2% higher with pad working. The ventilation performance of fans with identical specifications showed a variation by up to 13.0% in terms of the ventilating efficiency ratio. These results demonstrated that fans should be cleaned routinely, and belt tension should be checked to ensure that fan performance meets specifications. This can reduce the power consumption in greenhouses for environmental control. Moreover, reordering fan staging, so that the most efficient fans are used in areas of greatest demand, can also reduce ventilation energy costs.DOI: 10.3965/j.ijabe.20150801.014Citation: Zhang Z, Gates R S, Zou Z R, Hu X H. Evaluation of ventilation performance and energy efficiency of greenhouse fans. Int J Agric & Biol Eng, 2015; 8(1): 103－110.